2009
DOI: 10.1002/pits.20436
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of teacher and school psychologist knowledge of Attention‐Deficit/Hyperactivity Disorder

Abstract: The purpose of this study was to investigate teacher and school psychologists' knowledge of Attention‐Deficit/Hyperactivity Disorder (ADHD). One hundred thirty‐two kindergarten through 12th‐grade general education teachers, special education teachers, and school psychologists responded to a 24‐item questionnaire concerning treatment and possible causes of ADHD. The results supported the hypothesis that school psychologists' knowledge level of ADHD would be significantly greater than the knowledge level of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 23 publications
3
17
0
7
Order By: Relevance
“…Somewhat surprisingly, relatively few studies have examined whether special education teachers have greater levels of knowledge and/or training in ADHD than general education teachers (Jones and Chronis-Tuscano 2008;Weyandt et al 2009). Interestingly, Weyandt et al found that special education teachers did not have significantly greater knowledge of ADHD than general education teachers.…”
Section: Teacher Training In Adhdmentioning
confidence: 98%
“…Somewhat surprisingly, relatively few studies have examined whether special education teachers have greater levels of knowledge and/or training in ADHD than general education teachers (Jones and Chronis-Tuscano 2008;Weyandt et al 2009). Interestingly, Weyandt et al found that special education teachers did not have significantly greater knowledge of ADHD than general education teachers.…”
Section: Teacher Training In Adhdmentioning
confidence: 98%
“…Así, por ejemplo, Dryer et al (2006) encontraron mayor nivel de conocimientos en psicólogos y médicos que en maestros. Weyandt et al (2009) también hallaron superioridad en los conocimientos de los psicólogos escolares frente al profesorado general y especialista en educación especial. En el estudio de Massé et al (2009), los niveles más altos de conocimientos correspondieron a los psicólogos educativos y los más bajos al personal escolar compuesto por maestros, directores o pedagogos.…”
Section: Discussionunclassified
“…Dryer, Kiernan y Tyson (2006) encontraron concordancias entre psicólogos y médicos en lo que respecta a las características y causas del TDAH, mientras que los maestros poseen sobre estos temas mayor número de creencias erróneas que los dos grupos anteriores. Weyandt, Fulton, Schepman, Verdi y Wilson (2009) afirmaban que, si bien los psicólogos escolares deberían estar provistos de información relevante y actualizada sobre el diagnóstico y tratamiento del TDAH, la investigación sobre conocimientos de los psicólogos era prácticamente inexistente. En consecuencia, llevaron a cabo uno de los escasos estudios realizados sobre este colectivo, confirmando la hipótesis de que los psicólogos escolares poseen un mayor nivel de conocimientos sobre TDAH que los maestros generales o especialistas en educación especial.…”
Section: Introductionunclassified
“…Los sujetos con TDAH grave son los más frecuentemente referidos. 8,9 Dada la importancia de la información de los maestros, el DSM-5 requerirá la opinión de estos profesionales para establecer el diagnós-tico de TDAH.…”
unclassified